Using Steady-State Kinetics to Quantitate Substrate Selectivity and Specificity: A Case Study with Two Human Transaminases - Alessio Peracchi; Eugenia Polverini (Molecules, 2022)
We examined the ability of two human cytosolic transaminases, aspartate aminotransferase (GOT1) and alanine aminotransferase (GPT), to transform their preferred substrates whilst discriminating against similar metabolites. This offers an opportunity to survey our current understanding of enzyme selectivity and specificity in a biological context. Substrate selectivity can be quantitated based on the ratio of the kcat/KM values for two alternative substrates (the ‘discrimination index’). After assessing the advantages, implications and limits of this index, we analyzed the reactions of GOT1 and GPT with alternative substrates that are metabolically available and show limited structural differences with respect to the preferred substrates. The transaminases’ observed selectivities were remarkably high. In particular, GOT1 reacted ~106-fold less efficiently when the side-chain carboxylate of the ’physiological’ substrates (aspartate and glutamate) was replaced by an amido group (asparagine and glutamine). This represents a current empirical limit of discrimination associated with this chemical difference. The structural basis of GOT1 selectivity was addressed through substrate docking simulations, which highlighted the importance of electrostatic interactions and proper substrate positioning in the active site. We briefly discuss the biological implications of these results and the possibility of using kcat/KM values to derive a global measure of enzyme specificity.